Papillary Thyroid Microcarcinoma with a Large Cystic Dilated Lymph Node Metastasis to the Neck Mimicking a Branchial Cleft Cyst: A Potential Pitfall. (9th July 2015) - Ozdamar, Osman Ilkay; Acar, Gul Ozbilen; Kafkasli, Cigdem; Kalcioglu, M. Tayyar; Zenginkinet, Tulay; Tamer, H. Gonca
Abstract : Lateral cervical cystic mass in a young adult very rarely could be a first sign of an occult thyroid papillary microcarcinoma metastasis. In this paper, we presented a 37-year-old male patient whose preoperative 6 cm left lateral cervical cystic mass was initially diagnosed as branchial cleft cyst, but then the postoperative histopathological examination of the mass was revealed as papillary thyroid carcinoma metastasis. Preoperative fine needle aspiration biopsy was relevant with a branchial cleft cyst. In the left thyroid lobe there were 3 solid nodules with 4, 6, and 12 mm dimensions, respectively. One of the nodules had malignant well-differentiated cells diagnosed after fine needle aspiration biopsy. After total thyroidectomy, histopathologic evaluation of biopsy material's showed papillary thyroid microcarcinomas. This case indicates that especially in a young adult lateral cervical cystic mass should be carefully considered preoperatively for the possibility of metastatic occult thyroid carcinoma, especially for papillary carcinoma in differential diagnosis, and evaluation of the thyroid gland should be taken into account.